Properties of concrete with coarse aggregate using steel slag mixture from Ha Tinh Formosa steel plant - Dương, Trung Quốc; Trần, Thanh Nhàn; Trần, Thị Ngọc Quỳnh; Trần, Xuân Thạch; Nguyễn, Thanh Hải; Đỗ, Quang Thiên; Nguyễn, Hữu Đồng (Hue University Journal of Science: Natural Science, 2025)
In this study, a mixture based on the emission ratio of four types of steel slag from Hung Nghiep Formosa Ha Tinh Steel Plant (Formosa steel slag) was tested with the aim of serving as coarse aggregate for cement concrete. The results indicate that, although the particles are relatively smaller than the requirements for coarse aggregates for concrete according to the TCVN 7570:2006 standard, the physico-mechanical properties of the steel slag mixture, particularly crushing value, softening coefficient, abrasion resistance, and the proportion of flat and elongated particles, all meet the requirements for coarse aggregates for concrete, even for high-grade concrete (grade over 400). The design calculation for the concrete mix was carried out, and initial specimens of concrete using Formosa steel slag as coarse aggregates were produced. The results indicate that the concrete specimens, with the usage of cement and water conforming to the Ministry of Construction’s standards, achieved compressive strength after 28 days, exceeding the requirements for grade 400 concrete by 116% to 129%. Moreover, the density of the concrete meets the requirements for ultra-heavy concrete, offering numerous technical, economic, and environmental benefits. This makes the material highly suitable for use in manufacturing wave-breaking structures to prevent coastal erosion and protect coastal infrastructure.